Febrile convulsions in a national cohort followed up from birth. I–Prevalence and recurrence in the first five years of life. Issue 6478 (4th May 1985) - Verity, C M; Butler, N R; Golding, J
Abstract : Of 13 135 children followed up from birth to the age of 5 years, 303 (2.3%) had febrile convulsions. Prior neurological abnormality had been noted in 13. Of the 290 remaining children, 57 (20%) presented with a complex convulsion, and 103 children (35%) went on to have further febrile convulsions. The risk of further febrile convulsions varied with the age at first convulsion and the presence of a history of convulsive disorders in relatives. There were no significant differences between the sexes.